T1 relaxation time constants, influence of oxygen, and the oxygen transfer function of the human lung at 1.5T—A meta-analysis - Dietrich, Olaf; Gaass, Thomas; Reiser, Maximilian F. (European journal of radiology, 2017)
To pool and summarize published data from magnetic resonance longitudinal relaxation measurements of the human lung at 1.5T to provide a reliable basis of T1 relaxation time constants of healthy lung tissue both under respiration of room air and of pure oxygen. In particular, the oxygen-induced shortening of T1 was evaluated. The PubMed database was comprehensively searched up to June 2016 for original publications in English containing quantitative T1 data (at least mean values and standard deviations) of the lung parenchyma of healthy subjects (minimum subject number: 3) at 1.5T. From all included publications, T1 values of the lung of healthy subjects were extracted (inhaling room air and, if available, inhaling pure oxygen). Weighted mean values and standard deviations of all extracted data and the oxygen transfer function (OTF) were calculated. 22 publications were included with a total number of 188 examined healthy subjects. 103 of these subjects (from 13 studies) were examined while breathing pure oxygen and room air; 85 subjects were examined only under room-air conditions. The weighted mean value (weighted sample standard deviation) of the room-air T1 values over all 22 studies was 1196ms (152ms). Based on studies with room-air and oxygen results, the mean T1 value at room-air conditions was 1172ms (161ms); breathing pure oxygen, the mean T1 value was reduced to 1054ms (138 ms). This corresponds to a mean T1 reduction by 118ms (35ms) or 10.0 % (2.3 %) and to a mean OTF value of 1.22 (0.32)×10−3s−1/(%O2). This meta-analysis with data from 188 subjects indicates that the average T1 relaxation time constant of healthy lung tissue at 1.5T is distributed around 1200ms with a standard deviation of about 150 ms; breathing pure oxygen reduces this value significantly by 10 % to about 1050 ms.